Efficacy of Myofunctional Therapy Associated with Voice Therapy in the Rehabilitation of Neurogenic Oropharyngeal Dysphagia: a pilot study - Fraga, Bruno Francisco de; Almeida, Sheila Tamanini de; Santana, Márcia Grassi; Cassol, Mauriceia (International Archives of Otorhinolaryngology, 2018)
Introduction Dysphagia causes changes in the laryngeal and stomatognathic structures; however, the use of vocal exercises is poorly described.Objective To verify whether the therapy consisting of myofunctional exercises associated with vocal exercises is more effective in rehabilitating deglutition in stroke patients.Methods This is a pilot study made up of two distinct groups: a control group, which performed only myofunctional exercises, and an experimental group, which performed myofunctional and vocal exercises. The assessment used for oral intake was the functional oral intake scale (FOIS).Results The FOIS levels reveal that the pre-therapy median of the experimental group was 4, and increased to 7 after therapy, while in the control group the values were 5 and 6 respectively. Thus, the experimental group had a statistically significant difference between the pre- and post-therapy assessments (p = 0.039), which indicates that the combination of myofunctional and vocal exercises was more effective in improving the oral intake levels than the myofunctional exercises alone (p = 0.059). On the other hand, the control group also improved, albeit at a lower rate compared with the experimental group; hence, there was no statistically significant difference between the groups post-therapy (p = 0.126).Conclusion This pilot study showed indications that using vocal exercises in swallowing rehabilitation in stroke patients was able to yield a greater increase in the oral intake levels. Nevertheless, further controlled blind clinical trials with larger samples are required to confirm such evidence, as this study points to the feasibility of conducting this type of research.
Keywords: deglutition disorders; voice training; stroke